Extension and the Environment: Understanding Florida Residents’ Perceptions of Environmental Water-Related Topics - Caroline G. Roper; Alexa J. Lamm (EDIS)
By understanding Florida residents’ perceptions of water quality and quantity issues, Extension faculty can better communicate with them about water quantity and quality issues. This 4-page fact sheet explores Florida residents’ perceptions of water topics related to environmental issues. Written by Caroline G. Roper and Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, September 2014.